Innate immunity and immunotherapy for hemorrhagic shock - Huang, Qingxia; Gao, Song; Yao, Yao; Wang, Yisa; Li, Jing; Chen, Jinjin; guo, Chen; Zhao, Daqing; Li, Xiangyan (Frontiers in Immunology, 2022)
Hemorrhagic shock (HS) is a shock result of hypovolemic injury, in which the innate immune response plays a central role in the pathophysiology of the severe complications and organ injury in surviving patients. During the development of HS, innate immunity acts as the first line of defense, mediating a rapid response to pathogens or danger signals through pattern recognition receptors. The early and exaggerated activation of innate immunity, which is widespread in patients with HS, results in systemic inflammation, cytokine storm, and excessive activation of complement factors and innate immune cells, comprised of type II innate lymphoid cells, CD4+ T cells, natural killer cells, eosinophils, basophils, macrophages, neutrophils, and dendritic cells. Recently, compelling evidence focusing on the innate immune regulation in preclinical and clinical studies promises new treatment avenues to reverse or minimize HS-induced tissue injury, organ dysfunction, and ultimately mortality. In this review, we first discuss the innate immune response involved in HS injury, and then systematically detail the cutting-edge therapeutic strategies in the past decade regarding the innate immune regulation in this field; these strategies include the use of mesenchymal stem cells, exosomes, genetic approaches, antibody therapy, small molecule inhibitors, natural medicine, mesenteric lymph drainage, vagus nerve stimulation, hormones, glycoproteins, and others. We also reviewed the available clinical studies on immune regulation for treating HS and assessed the potential of immune regulation concerning a translation from basic research to clinical practice. Combining therapeutic strategies with an improved understanding of how the innate immune system responds to HS could help to identify and develop targeted therapeutic modalities that mitigate severe organ dysfunction, improve patient outcomes, and reduce mortality due to HS injury.